PUBLIC AUTHORITIES’ POWERS IN CONSUMER PROTECTION IN THE VISEGRAD FOUR STATES AND THE IMPACT OF EU LAW - Janderová, Jana; Brodská, Daniela (SGEM, 2024)
This study investigates the differences in national approaches to consumer protection, focusing on the powers of public authorities stemming from national legislation and the impact of EU regulations on the consumer protection landscape in the V4 countries. The research employs a qualitative methodology to analyse national laws and the implemented EU directives, and the field of full harmonisation with a particular emphasis on Regulation (EU) 2017/2394. The objectives of the study include understanding the minimum harmonization of powers given to public authorities responsible for consumer protection within the EU, assessing the practical impact of this harmonization on the V4 countries, and comparing the consumer protection legislation in the V4 countries with the directives implemented by the EU and regulation (EU) 2017/2394. The findings of this research could provide valuable insights into the effectiveness of consumer protection laws and regulations in the V4 countries and the EU. Through this comprehensive analysis, the paper aims to contribute to the discourse on consumer protection and the role of inspection authorities in enforcing consumer rights. It seeks to provide valuable insights for policymakers, regulators, and consumer rights advocates.
PRAVOMOCI PRÁVNÍCH ORGÁNŮ V OCHRANĚ SPOTŘEBITELŮ VE STÁTECH VISEGRÁDSKÉ ČTYŘKY A VLIV PRÁVA EU NA NĚ
Keywords: Czech Trade Inspection Authority; consumer protection; public authority; state control; Česká obchodní inspekce; ochrana spotřebitele; správní orgán; veřejná kontrola